(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
A microstrip slot antenna for C Band has been proposed with compact structure and suppressed back radiation. In this paper, the feeding technique used is aperture coupling with a modification that patches and the feed line are positioned below the substrate and the slot is etched above the substrate. The position of the patches along the slot axis is kept at the negative peak of the standing wave distributions to generate the voltage null on the slot line so as to have a 180Âº phase shift in the centre of the patch hence achieving better front to back ratio. Also the gain of 6.774dB is achieved in this design. The results are validated by simulation measurements.